High-throughput analysis of microbiomes in a meat processing facility: are food processing facilities an establishment niche for persisting bacterial communities? - Zhaohui S. Xu; Vi D. Pham; Xianqin Yang; Michael G. Gänzle (Microbiome)
Abstract Background Microbial spoilage in meat impedes the development of sustainable food systems. However, our understanding of the origin of spoilage microbes is limited. Here, we describe a detailed longitudinal study that assesses the microbial dynamics in a meat processing facility using high-throughput culture-dependent and culture-independent approaches to reveal the diversity, dispersal, persistence, and biofilm formation of spoilage-associated microbes. Results Culture-dependent and culture-independent approaches revealed a large diversity of microbes within the meat facility, including 74 undescribed bacterial taxa and multiple spoilage-associated microbes. Ten out of 10 reconstituted microbial communities formed biofilms, and the biofilm biomass was generally higher at 4 °C than at 25 °C. Isolates obtained at different sampling times or from different sampling sites that differed in fewer than 10 genome-wide single-nucleotide polymorphisms were considered the same (persistent) strains. Strains of Carnobacterium maltaromaticum and Rahnella rivi persisted over a period of 6 months across sampling sites and time, stemming from floor drains in the cooler room. Meat isolates of Carnobacterium divergens, Rahnella inusitata, and Serratia proteamaculans originated from food contact and non-food contact environments of the packaging area. Conclusions Culture-dependent isolation, complemented by culture-independent analyses, is essential to fully uncover the microbial diversity in food processing facilities. Microbial populations permanently resided within the meat processing facility, serving as a source of transmission of spoilage microbes. The ability of these microbes to coexist and form biofilms facilitates their persistence. Our data together with prior data on persistence of Listeria monocytogenes indicates that microbial persistence in food processing facilities is the rule rather than an exception. Video Abstract